Self-administered versus clinician-performed BinaxNOW COVID rapid test: a comparison of accuracy - Mary Jane E. Vaeth; Minahil Cheema; Sarah Omer; Ishaan Gupta; Kristie J. Sun; Asia Mitchell; Maryam Elhabashy; Maisha Foyez; Aamna Cheema; Binish Javed; Sophia Purekal; Resham Rahat; et al. (Microbiology Spectrum, 2024)
ABSTRACTWe conducted a single-center study at a free community testing site in Baltimore City to assess the accuracy of self-performed rapid antigen tests (RATs) for COVID-19. Self-administered BinaxNOW RATs were compared with clinician-performed RATs and against a reference lab molecular testing as the gold standard. Of the 953 participants, 14.9% were positive for SARS- CoV-2 as determined by RT-PCR. The sensitivity and specificity were similar for both self- and clinician-performed RATs (sensitivity: 83.9% vs 88.2%, P = 0.40; specificity: 99.8% vs 99.6%, P = 0.6). Subgroup comparisons based on age and race yielded similar results. Notably, 5.2% (95% CI: 1.5% to 9.5%) of positive results were potentially missed due to participant misinterpretation of the self-test card. However, the false-positive rate for RATs was reassuringly comparable in accuracy to clinician-administered tests. These findings hold significant implications for physicians prescribing treatment based on patient-reported, self-administered positive test results. Our study provides robust evidence supporting the reliability and utility of patient-performed RATs, underscoring their comparable accuracy to clinician-performed RATs, and endorsing their continued use in managing COVID-19. Further studies using other rapid antigen test brands are warranted.IMPORTANCEAccurate and accessible COVID-19 testing is crucial for effective disease control and management. A recent single-center study conducted in Baltimore City examined the reliability of self-performed rapid antigen tests (RATs) for COVID-19. The study found that self-administered RATs yielded similar sensitivity and specificity to clinician-performed tests, demonstrating their comparable accuracy. These findings hold significant implications for physicians relying on patient-reported positive test results for treatment decisions. The study provides robust evidence supporting the reliability and utility of patient-performed RATs, endorsing their continued use in managing COVID-19. Furthermore, the study highlights the need for further research using different rapid antigen test brands to enhance generalizability. Ensuring affordable and widespread access to self-tests is crucial, particularly in preparation for future respiratory virus seasons and potential waves of reinfection of SARS-CoV-2 variants such as the Omicron variant.